Identification of Phytochemical Compounds Aquatic Plants in Pematangsiantar - Herna Febrianty Sianipar; Apriani Sijabat; Christa Voni Roulina Sinaga; Mardame Pangihutan Sinaga; Welmar Olfan Basten Barat (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Aquatic plants are float on the surface of the water and easy to continue to grow and can even be detrimental to the environment and other aquatic organisms it they have expanded, so it is necessary to use them to reduce losses. One way to use aquatic plants is to know the phytochemical compounds of these aquatic plants, so that they can be used as medicinal plants. The purpose of this study was to determine the phytochemical compounds found in aquatic plants such as water eceng gondok (Eichhornia crassipes), genjer (Limnocharis flava) dan kiambang (Salvinia molesta). This research was conducted at the water resources management laboratory University of HKBP Nommensen Pematangsiantar with the extraction method from the leaves. Phytochemical test carried out consisted of alkaloids, flavonoids, saponins, phenolics, tannins, and vitamin c. phytochemical test results of alkaloids, flavonoids, phenolics and vitamin c were found in the three types of leaves the aquatic plants, while saponins were not found in genjer and eceng gondok, then tannins were not found in genjer. The highest phytochemical content is found in kiambang, and the lowest phtochemical content is found in genjer plants. Furthermore, it is necessary to test the antibacterial activity of aquatic plants originating from the water of Pematangsiantar city.